PERILAKU PENCARIAN INFORMASI SISWA DAN MAHASISWA DALAM MEMENUHI KEBUTUHAN INFORMASI DI DINAS PROVINSI SUMATERA SELATAN - Muhammad Ilham (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to analyze in depth the information-seeking behavior of students and college students in fulfilling their information needs at the South Sumatra Provincial Library Service. This research employs a qualitative descriptive approach using observation, in-depth interviews with six informants, and documentation as data collection techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal significant differences between school students and university students in their information-seeking behavior. School students tend to remain at basic stages such as starting and browsing, lacking systematic planning and experiencing difficulties in utilizing information retrieval tools such as OPAC. In contrast, university students demonstrate more advanced behaviors, including differentiating, monitoring, and verifying, indicating a more selective and strategic approach in processing information.